Determining RBE for development of lung fibrosis induced by fractionated irradiation with carbon ions utilizing fibrosis index and high-LET BED model. (January 2019) - Zhou, Cheng; Jones, Bleddyn; Moustafa, Mahmoud; Yang, Bing; Brons, Stephan; Cao, Liji; Dai, Ying; Schwager, Christian; Chen, Ming; Jaekel, Oliver; Chen, Longhua; Debus, Juergen; et al.
Highlights: Determining normal tissue tolerance of organs at risk is of utmost importance for the success of carbon ion radiotherapy (CIRT). This manuscript is the first report on experimental RBE for development of lung fibrosis assessed by quantitative CT after fractionated CIRT. We further propose RBE estimation by integrating RBEmax and α/βL based modified high-LET BED model. This model was found to well predict RBE but is sensitive to the uncertainties of α/βL estimates from the reference photon irradiation. Our findings will contribute to a more precise knowledge of RBE as well as the fractionated dose effects of carbon ion therapy on normal lung tissue. Abstract: Background and purposes: Carbon ion radiotherapy (CIRT) with raster scanning technology is a promising treatment for lung cancer and thoracic malignancies. Determining normal tissue tolerance of organs at risk is of utmost importance for the success of CIRT. Here we report the relative biological effectiveness (RBE) of CIRT as a function of dose and fractionation for development of pulmonary fibrosis using well established fibrosis index (FI) model. Materials and Methods: Dose series of fractionated clinical quality CIRT versus conventional photon irradiation to the whole thorax were compared in C57BL6 mice. Quantitative assessment of pulmonary fibrosis was performed by applying the FI to computed tomography (CT) data acquired 24-weeks post irradiation. RBE was calculated as the ratio of photon to CIRT dose required for the same level of FI. Further RBE predictions were performed using the derived equation from high-linear energy transfer biologically effective dose (high-LET BED) model. Results: The averaged lung fibrosis RBE of 5-fraction CIRT schedule was determined as 2.75 ± 0.55. The RBE estimate at the half maximum effective dose (RBEED50 ) was estimated at 2.82 for clinically relevant fractional sizes of 1–6 Gy. At the same dose range, an RBE value of 2.81 ± 0.40 was predicted by the high-LET BED model. The converted biologically effective dose (BED) of CIRT for induction of half maximum FI (BEDED50 ) was identified to be 58.12 Gy3.95 . In accordance, an estimated RBE of 2.88 was obtained at the BEDED50 level. The LQ model radiosensitivity parameters for 5-fraction was obtained as αH  = 0.3030 ± 0.0037 Gy −1 and βH  = 0.0056 ± 0.0007 Gy −2 . Conclusion: This is the first report of RBE estimation for CIRT with the endpoint of pulmonary fibrosis in-vivo . We proposed in present study a novel way to mathematically modeling RBE by integrating RBEmax and α/βL based on conventional high-LET BED conception. This model well predicted RBE in the clinically relevant dose range but is sensitive to the uncertainties of α/β estimates from the reference photon irradiation (α/βL ). These findings will assist to eliminate current uncertainties in prediction of CIRT induced normal tissue complications and builds a solid foundation for development of more accurate in-vivo data driven RBE estimates.